Einfluss neuer Techniken in der Bildgebung der Niere - Uder, Michael; Heinrich, Marc Christopher; Jäger, Florian; Hornegger, Joachim; Schmieder, Roland; Janka, Rolf Matthias (Nephrologe, 2009)
Computed tomography and magnetic resonance imaging have developed very rapidly in recent years. Today these methods are capable not only of morphological assessment of the kidneys but also provide data of a functional nature. Urography by MRI and CT have long been established in clinical routine. Other techniques such as blood level oxygenation-dependent (BOLD), diffusion-weighted, and renal perfusion imaging using MRI or CT are used almost exclusively for research purposes, but they also have many possibilities for renal applications under study conditions in diagnostics and for monitoring vascular and parenchymatous disorders. © 2009 Springer-Verlag.